Conserved cell‐type specific signature of resilience to Alzheimer's disease nominates role for excitatory cortical neurons. (20th December 2022) - Telpoukhovskaia, Maria; Hadad, Niran; Gurdon, Brianna; Dai, Miko; Ouellette, Andrew R; Neuner, Sarah; Dunn, Amy R; Hansen, Shania L; Wu, Yiyang; Dumitrescu, Logan; O'Connell, Kristen MS; Dammer, Eric B; et al.
Abstract: Background: Alzheimer's disease (AD), the leading cause of dementia, affects millions of people worldwide. With no disease‐modifying medication currently available, the human toll and economic costs are rising rapidly. Under current standards, a patient is diagnosed with AD when both cognitive decline and pathology (amyloid plaques and neurofibrillary tangles) are present. Remarkably, some individuals who have AD pathology remain cognitively normal. Uncovering factors that lead to "cognitive resilience" to AD is a promising path to create new targets for therapies. However, technical challenges discovering novel human resilience factors limit testing, validation, and nomination of novel drugs for AD. Method: In this study, we use single‐nuclear transcriptional profiles of postmortem cortex from human individuals with high AD pathology who were either cognitively normal (resilient) or cognitively impaired (susceptible) at time of death, as well as mouse strains that parallel these differences in cognition with high amyloid. Result: Our cross‐species discovery approach highlights a novel role for excitatory layer 4/5 cortical neurons in promoting cognitive resilience to AD, and nominates several resilience genes that include ATP1A1, GABRB1, PTK2, and ROCK2 . Nominated resilience genes were tested for replication in orthogonal data sets and confirmed to be correlated with cognitive resilience. Additionally, we identified several potential mechanisms of resilience, including regulation of membrane potential, axonal and dendritic growth, and general increase of protein cycle, potentially of membrane proteins. Conclusion: Because our discovery of resilience‐associated genes in layer 4/5 cortical neurons originates from an integrated human and mouse transcriptomic space from susceptible and resilient individuals, we are positioned to test causality and perform mechanistic, validation, and pre‐clinical studies in our human‐relevant AD‐BXD mouse panel.